Preseason prognostic factors for injuries and match Llss in collision sports: A systematic review - Watanabe, K.; Kitamura, T.; Takasaki, H. (International Journal of Sports Medicine, 2023)
This study aimed to identify which preseason factors had strong evidence of risks for physical injury during the season of collision sports including rugby, American football, and Australian rules football using qualitative synthesis. Pubmed, EMBASE, MEDLINE, SPORTDiscus, Scopus, and the Cochrane Library were reviewed. Eligibility criteria for selecting studies were: studies involving the collision sports; prospective cohort studies; and studies with outcomes of relative risks, odds ratios, and correlations between players` preseason conditions and injury during the season. The risk of bias based on the Scottish Intercollegiate Guidelines Network quality checklists for cohort studies was assessed in 57 studies. The current study identified strong evidence that 1) anthropometric characteristics (body mass index and estimated mass moment of inertia of the body around a horizontal axis through the ankle), which are calculated with weight and height; 2) physical function, in particular for the trunk and lower limb (trunk-flexion hold and wall-sit hold); and 3) Oswestry Disability Index disability, which is a patient-reported outcome measure for disability due to low back pain, were positive prognostic factors for injury during the collision sports season, regardless of playing experience.